Estudos in vitro e in silico do mecanismo de ação vasorrelaxante da amida sintética (E)-N-(4-metoxifenetil)-3-(tiofen-2-il)acrilamida (MFTA) em aorta de rato - Silva, Antônio Raphael Lima de Farias Cavalcanti (2022)
(E)-N-(4-methoxyphenethyl)-3-(thiophen-2-yl)acrylamide (MFTA) is a synthetic thiophenic amide, in which the furan ring oxygen has been replaced by sulfur, forming a thiophene ring, creating a new molecule. Several amide activities have been reported in smooth muscle, including vasorelaxant activity in rat aorta. With molecular docking it is possible to predict the best orientation of one molecule to a second one, when they are coupled, forming a complex. Considering that MFTA in a previous work presented a non-selective spasmolytic effect in tonic and phasic smooth muscle models, being more potent in rat aorta, it was decided to characterize its vasorelaxant mechanism of action through in vitro and in silico studies. The aorta of Wistar rats was sectioned into rings and suspended in isolated organ baths under appropriate conditions, and isometric contractions were monitored. MFTA was subjected to molecular docking (MD) in Molegro Virtual Docker v.6.0.1, using voltage-gated calcium channel (CaV) and Rho-associated protein kinase (ROCK) complexed with nifedipine and Y-27632, respectively, obtained from the Protein Data Bank, having as reference the energy value of the Moldock and Rerank score algorithms (kcal/mol). All experimental protocols (n = 5) were approved by the Ethics Committee for the Use of Animals at UFPB (8073300419). MFTA equipotently and concentration-dependently relaxed the rat aorta pre-contracted with 3 x 10-7 M phenylephrine, both in the presence (Emax = 100% and EC50 = 1.1 ± 0.2 x 10-4 M ) and absence (Emax = 100% and EC50 = 1.3 ± 0.3 x 10-4 M) of functional endothelium, suggesting that its vasorelaxant effect appears to be due to a mechanism independent of endothelium-derived relaxing factors. Thus, it was decided to evaluate the participation of K+ and CaV channels in the vasorelaxant effect of MFTA. It was observed that the amide relaxed the pre-contracted aorta with 30 (Emax = 95.4 ± 4.6% and EC50 = 1.9 ± 0.2 x 10-4 M) or 80 mM (Emax = 98.7 ± 1.3% and EC50 = 8.3 ± 0.7 x 10-5 M) of KCl, being about twice more potent when these rings were pre-contracted with high concentrations of KCl, indicating a possible participation of CaV. This hypothesis was confirmed by the observation that amide (10-5–3 x 10-4 M) inhibited in a concentration-dependent manner the contractions induced by CaCl2 in depolarizing medium nominally without calcium, with shift of the control curve to the right and reduction of the Emax from 100% (control) to 95.6 ± 4.5; 68.4 ± 5.2; 54.0 ± 3.4 and 19.4 ± 3.5%, respectively. The EC50 values of CaCl2 changed from 2.0 ± 0.2 x 10-3 M (control) to 1.5 ± 0.2 x 10-3; 2.8 ± 0.2 x 10-3; 7.0 ± 1.2 x 10-3; 1.2 ± 0.5 x 10-4 M, respectively. In addition, MFTA relaxed the pre-contracted aorta in a concentration-dependent manner with 3 x 10-7 M of S-(-)-Bay K8644, a CaV1 agonist (Emax = 100% and EC50 = 6.3 ± 1.6 x 10-5 M), indicating a possible inhibition of Ca2+ influx through CaV1. The participation of the ROCK pathway was also investigated and it was observed that there was no difference in the efficacy or in the relaxing potency of MFTA in the presence of 10-6 M of Y-27632 (Emax = 100% and EC50 = 5.4 ± 1.1 x 10-5 M), discarding the participation of this pathway in the in vitro vasorelaxant effect of the amide. In silico studies, in vitro assays for blocking Cav can be confirmed, as evidenced by the more negative energetic values of MFTA (-132.99 and -111.60) when compared to nifedipine (-81.77 and 122.98) for Moldock and Rerank score respectively. For ROCK, in silico studies were consistent with in vitro studies only in the Rerank score function, since MFTA (-60.64) did not present more negative energy than Y-27632 (-73.35). Therefore, MFTA has a vasorelaxant effect by blocking Cav1, so that the most negative score of energy values in MD corroborates the confirmation of this hypothesis.